Tanaman Kecombrang sebagai Ide Dasar Penciptaan Motif Batik Tulis - Dhita Hartina P. Daulay; Misgiya Misgiya (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
Indonesian National Arts are different from other countries. One of them is textile craft art, which includes batik craft art, which was recognized by UNESCO as an original Indonesian cultural heritage on October 2, 2009. Batik is the art of drawing on clot . Hand-drawn batik is batik that is produced using a canting tulis which is used as a tool in placing wax liquid on the cloth. To create this work, the author uses the creation method from Sp. Gustami which consists of 3 stages, namely: Exploration, Design, and Realization. The results of the creation of this hand-drawn batik work produced 12 batik works in the form of two-dimensional works of various sizes. The types produced from this work are: Hijab, Long Cloth and Wall Decorations. Batik works have aesthetic value (beauty) namely the combination of Torch Ginger Plants. Torch Ginger Plants are used as the main motif in this batik work and other motifs are isen-isen. The process of creating written batik works that begins with the initial steps of making motifs on paper, transferring patterns from paper to cloth, the canting process, coloring batik, locking colors, and ngelorod batik. The process of creating written batik works that begins with the initial steps of making motifs on paper, transferring patterns from paper to cloth, the canting process, coloring batik, locking colors, and ngelorod batik.